Deep percolation in greenhouse-cultivated celery using the technique of subsurface film strips placement - Du, Zhida; Shao, Longtan; Ma, Mingchao (Spanish Journal of Agricultural Research, 2014)
To reduce the deep percolation during greenhouse vegetable cultivation, the technique of subsurface film strips placement was tested. Four treatments with two kinds of cross-sections (flat and U-shaped) and two different spacings (10 cm and 40 cm) of subsurface film strips were arranged in a greenhouse before planting celery. At the same time, a non-film treatment was arranged for comparison. Soil water content was measured and irrigation time was adjusted according to the soil water content. Evapotranspiration of celery during growth was calculated by the method of energy balance and the deep percolation was calculated by the equation of water balance. Deep percolation was reduced in all experimental treatments. Greater reduction in deep percolation was observed when using U-shaped cross-section strips compared with that using the flat cross-section strips. In addition, greater reduction in deep percolation was observed when the spacing between the film strips was smaller. The results of this test showed that the technique of subsurface film strips placement can reduce deep percolation and conserve irrigation water for greenhouse vegetables cultivation. However, the optimal layout variables for the use of the technique of subsurface film strips placement need further experimental and numerical analysis.